Synergistic antimicrobial action and effect of active chitosan-gelatin biopolymeric films containing Thymus vulgaris, Ocimum basilicum and Origanum majorana essential oils against Escherichia coli and Staphylococcus aureus - de Souza, Victoria Vilaça Martins Alencar; Crippa, Bruna Lourenço; de Almeida, Jaqueline Milagres; Iacuzio, Raiza; Setzer, William N.; Sharifi-Rad, Javad; Silva, Nathália Cristina Cirone (Cellular and Molecular Biology, 2020)
To replace synthetic preservatives and expand green consumption, several essential oils have been tested in foods and food packaging due to their antimicrobial properties. This study aimed to analyze the synergistic antimicrobial action of a chitosan-gelatin based active biopolymers with the addition of essential oils (EOs). The antimicrobial agents were tested against foodborne microorganisms Staphylococcus aureus and Escherichia coli strains. The antibacterial activity of Thymus vulgaris, Ocimum basilicum, Origanum majorana, and the synergistic interactions among them were assessed according to the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) using the microdilution method. Chitosan-gelatin based active biopolymers were developed, and 23% (w/w) of each essential oil and combined oils were added. The antimicrobial effect of active films was measured using the disk diffusion method. Active films with the addition of essential oils have potential applications as active packaging agents, especially those that demonstrated inhibition zones. Combined EOs can be used to enhance the antimicrobial activity, ensuring reduced doses used in active packaging and decreasing the association with adverse sensory characteristics.